Middle School Students' Realistic Consideration of Problematic Problems - Gyuhee Yi; Jihyun Lee (Korea Society of Educational Studies in Mathematics, 2021)
This study aims to explore how 'sensitively' Korean middle school students consider realistic contexts while solving problematic problems. Six pairs of word problems were collectively administered to 85 students in third grade during a mathematics lesson, and follow-up interviews were conducted with 11 students. The survey found that the proportion of students who solved the problems by sensitively considering real-world knowledge was not high (22%). In the follow-up interviews, the students reported that they would think of mathematics separately from real-world situations. An analysis of the students' unrealistic reactions to real-life problems has implications for the practice of school mathematics regarding real-life word problems.